Pulmonary artery pseudoaneurysm-induced massive hemoptysis after chemotherapy combined with tislelizumab for lung squamous cell carcinoma: a case report - Yang, Xue-Jiao; Wu, Yong-Juan; Wang, Jing-Zhong; Zheng, Yu-Lan; Li, Xiao-Qi (Frontiers in Medicine, 2025)
Lung squamous cell carcinoma (SCC) is a subtype of non-small cell lung cancer with high incidence and mortality rates. While chemotherapy and immune checkpoint inhibitors (ICIs) have become crucial treatment options for SCC, these may be associated with unforeseen complications. Here, we present a 65-year-old male of hemoptysis caused by a pulmonary artery pseudoaneurysm (PAP) after chemotherapy combined with tislelizumab for lung SCC. After confirmation with angiography, successful embolization was performed to occlude the pseudoaneurysm and proximal artery. To our knowledge, this is the first reported case of PAP formation after chemotherapy combined with tislelizumab for lung SCC.